Atomism or holism: Evidential Evaluation in China's Exclusionary Rule of Illegally Obtained Evidence. (3rd July 2017) - Mou, Luye
Abstract : China's exclusionary rule of illegally obtained evidence does not specify how to determine the (un)lawfulness of disputed evidence. The exclusionary rule, undergirded by atomism in Anglo-American countries, evinces a holistic approach of evidential evaluation adopted in China's legislation and practice. Holism in the "trial within trial" derives from judges' zealous pursuit of truth and a mandate to prevent miscarriages of justice. When judges follow a holistic approach to determine the lawfulness of disputed evidence, independent values of the exclusionary rule would be compromised. More problematically, the psychological effects of coherence shifts make it more difficult to exclude evidence. Nonetheless, institutional tensions between China's exclusionary rule and other mechanisms provide challenges and opportunities for improving our procedural and evidentiary rules in a global perspective.